Acceptance of the COVID-19 vaccine in Generation Z: A cross-sectional study in Southeast Sulawesi, Indonesia - Hadiwijaya, Chevin Ramadhan; Analuddin, Muhammad Imam Zan Zabiyla; Sudayasa, Ayikacantya; Akbar, Muhammad Hoki; Ahmad, Lilyana Aritonia; Saimin, Juminten (Public Health of Indonesia, 2021)
Background: Adequate health systems and effective strategies are needed to increase trust and acceptance in vaccines. Generation Z is more concerned with environmental issues related to the pandemic situation.Objective: This study aimed to assess the acceptance of the COVID-19 vaccine in Generation Z.Methods: This was an observational analytical study with a cross-sectional design on generation Z in Southeast Sulawesi, Indonesia, from May to July 2021. The samples were taken by cluster sampling using faculty classification. Data was collected using a questionnaire with a google form, included the characteristics, knowledge regarding COVID-19 and vaccine, and the media information.Results: There were 396 participants. Most of them were <20 years (52.6%), female (74.8%), and Muslim (93.7%). About 61.6% live outside the city and had insurance (77.3%). Half of the participants knew the COVID-19 symptoms (51.26%), some participants were hesitant (11.8%) and did not even know (0.76%). Almost all participants were aware of the COVID-19 vaccination program (99.2%), benefits (95.2%), side effects (84.1%), and knew the contents of the COVID-19 vaccine (62.1%). Most of them were willing to take the COVID-19 vaccine (77.8%). However, 17.93% were hesitant, and 4.29% were unwilling to participate. Most participants were not trusting vaccines (43.9%), did not feel the need (29.3%), and felt access was not easy (26.8%). Most of them used social media to get information about COVID-19 (89.1%).Conclusion: Generation Z has a good acceptance of the COVID-19 vaccine, even though there are still doubts and rejects. Accurately and sustainable information is needed.